Shoulder Isokinetic Strength Balance Ratio in Overhead Athletes: A Cross-Sectional Study - Valentine Zimermann Vargas; Caroline Motta; Rodrigo Luiz Vancini; Claudio Andre Barbosa de Lira; Marilia Santos Andrade (North American Sports Medicine Institute, 2021)
# Background Studies have grouped different overhead sports and evaluated together the isokinetic strength of shoulder internal (IR) and external (ER) rotator muscles. However, muscular adaptations could be a consequence of the specific sport, and some strength imbalance between these muscles may exist as a consequence of the muscular demand unique to the sport. Therefore, grouping different overhead sports together may not be adequate. # Purpose To compare strength balance ratios between different overhead sports (volleyball, handball, swimming, judo, baseball, softball, functional movements performed at high-intensity interval training, and tennis) with a control athletic group (no overhead group). # Study design Cross-sectional study. # Methods A total of 237 athletes were submitted to isokinetic shoulder strength tests. The isokinetic concentric and eccentric peak torque values of shoulder internal IR and external ER rotator muscles were measured. Conventional (CR) and functional strength ratios (FR) were calculated. # Results There were no significant differences between the sports for the CR in the male group. Female softball athletes (90.4±13.6%) had a significantly higher CR than judo (67.3±6.9%), volleyball (74.9±15.9%), and swimming athletes (70.3±8.7%). In the female group, judo athletes had lower FR values (0.76±0.19) than soccer athletes (1.31±0.35), volleyball athletes (1.24±0.27), functional movements performed at high intensity (1.10±0.1), and softball athletes (1.40±0.39). Female handball athletes also had a lower FR (0.99±0.25) than soccer athletes (1.31±0.35) and softball athletes (1.40±0.39). Male handball (0.90±0.23), tennis (0.86±0.30), and judo (0.68±0.22) athletes had lower FR values than soccer athletes (1.20±0.21) and volleyball athletes (1.25±0.28). # Conclusions CR for males may be analyzed together, as there were no significant differences between them. However, for females, the CR for softball athletes should be analyzed individually. As there were several differences between the overhead sports according to the FRs, the authors suggest caution in grouping overhead athletes across multiple sports. These results could have important implications for the design of injury prevention and rehabilitation programs associated with the shoulder joint in overhead sports. # Level of Evidence 3